Pathogenesis of abdominal aortic aneurysms from the vascular surgeon perspective – knowledge summary - Hauzer, Willy; Gnus , Jan; Hauzer, Paula; Rosińczuk, Joanna (Journal of Education, Health and Sport, 2022)
Abdominal aortic aneurysms (AAA) affect 2.4% of the population, with men being five times more likely to be affected than women. The development of AAA is linked to changes in the elastin and vascular wall collagen. The enzymes that damage the cell wall are called metalloproteinases. AAA forms as a result of damage to elastic fibres and the loss of the property of reversible deformation of the aortic wall. The degradation of elastin and other stem proteins in the aortic wall is caused by metalloproteinases and serine proteases, accompanied by cysteine proteases and asparagine proteases. Increased calprotectin levels are observed in AAA patients in comparison to patients with a healthy aorta. A significant role in the pathogenesis of AAA and its rupture is played by inflammatory response cells; proteases of the tissue plasma coagulation and fibrinolysis. Plasminogen activator and plasmin accelerate the degradation of the aortic wall. Microbial involvement of C. pneumoniae, Helicobacter pylori, CMV, and HIV is considered in this inflammatory reaction. The local activation of platelets and the plasma coagulation system leads to the formation of a mural thrombus filling the lumen of the aneurysm. The mural thrombus shows a high tissue factor (TF) activity. The formation of AAA is conditioned by a combination of multiple factors. The factors impacting the formation of AAA discovered so far include genetic factors, sex, age, lifestyle (abuse of alcohol, tobacco misuse, obesity, stress), health conditions (hypertension, high cholesterol level, atherosclerosis), and infectious factors: bacteria, viruses, and other microorganisms.